Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1177/1468087411409309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen addition under lean and diluted conditions on combustion characteristics and emissions in a spark-ignition engine

Abstract: Experimental investigations on the effects of hydrogen addition to spark-ignition (SI) engines running under lean and diluted conditions are presented in this paper. Experiments were carried out in a mono-cylinder SI engine with different rates of nitrogen dilution (0 to 20 per cent by volume in the total mixture) and hydrogen/iso-octane blends (from 0 to 80 per cent by volume in the fuel). The study of the impact of hydrogen addition on combustion characteristics and emissions was performed for two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Besides in a previous study [26], it was shown, using two planes of visualization, that the flame mainly propagates in the horizontal direction especially after reaching the piston. Moreover, the work of Tahtouh et al [56,57] in the same optical engine showed that both direct visualization and tomography give the same trends regarding flame growth. Therefore, comparing the flame growth behavior for different air-fuel mixtures seems to be possible even if the two techniques will not give the same absolute values.…”
Section: Experimental Set-upmentioning
confidence: 91%
“…Besides in a previous study [26], it was shown, using two planes of visualization, that the flame mainly propagates in the horizontal direction especially after reaching the piston. Moreover, the work of Tahtouh et al [56,57] in the same optical engine showed that both direct visualization and tomography give the same trends regarding flame growth. Therefore, comparing the flame growth behavior for different air-fuel mixtures seems to be possible even if the two techniques will not give the same absolute values.…”
Section: Experimental Set-upmentioning
confidence: 91%
“…The result showed that at a fixed engine load, HC and CO emissions decrease with an increase in the hydrogen fraction in the intake mixture, while NO x emissions are mainly affected by the equivalence ratio and by the amount of dilution. 23 Modeling of IC engines is continuously growing and bases of the most of recent simulation investigations developed through zero-or one-dimensional (0D/1D) methods. [24][25][26] Although, in recent years, due to the vast calculative resources, studies have a desire to use threedimensional (3D) computational fluid dynamics (CFD) modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Flame speed is a sizing parameter to be considered in the design of energetic industrial systems such as IC engines [1,2] and gas turbines [3]. Indeed, this physicochemical property of a combustible mixture notably affects the heat release rate such as the flame stabilization.…”
Section: Introductionmentioning
confidence: 99%